(untitled) (Research, Society and Development, 2023)
Objective: To identify emotional changes in students completing the Physiotherapy course at a public institution of higher education. Methodology: Cross-sectional, observational and descriptive quantitative study, carried out with Physical Therapy students from a public institution of higher education located in Teresina - PI. A sociodemographic questionnaire and the Depression, Anxiety and Stress Scale (DASS 21) were used. Students regularly enrolled in the 9th and 10th period of graduation, aged 18 years or older and of both sexes, participated in the study. For data processing and analysis, the IBM Statistical Package for the Social Sciences version 20.0 program was used. Results: The sample consisted of 30 students, most of whom were female (86.7%) with a mean age of 23.83 ± 1.34. A significant prevalence of symptoms of anxiety (70.1%), stress (86.6%) and depression (73.3%) was found. Being the symptoms of stress and depression, the most prevalent emotional alterations, indicating 13 (43.3%) in the moderate phase and 13 (43.3%) in the severe phase, respectively. There was a significant difference in the anxiety aspect with the variables marital status and the practice of physical exercises, as well as in stress with the race variable. Conclusion: Senior Physiotherapy students had a higher prevalence of stress and depression symptoms. It is hoped that the results can contribute to the design of early identification strategies and interventions leading to the promotion of mental health for this public.